SISTEM PAKAR DIAGNOSA HAMA DAN PENYAKIT TANAMAN HOLTIKULTURA - Imelda Sri Dumayanti (Universitas Methodist Indonesia, 2020)
Consultation with someone who has expertise in a particular field in solving a problem is the right choice to get the best answers, suggestions, solutions, decisions or conclusions. Technological developments have an influence on developments in various sectors and technological advances have a lot of influence in the work process in agriculture, where a lot of agricultural equipment is developed so that the agricultural work process can be completed properly and provide better results in terms of quality and quantity. One technology that is widely developed is a technique that is able to adopt human thinking processes and ways, namely artificial intelligence technology (artificial intelligence). An expert system is one part of artificial intelligence that contains knowledge and experience that is entered by one or many experts into one knowledge. so that farmers can use the system to determine the right solution to the existing problems.